THE FACTORS INFLUENCING THE ACTUAL USE OF MOBILE LEARNING AMONG STUDENTS IN MALAYSIAN UNIVERSITY - Mohamad Nizam Adhaa Kamarudin; Adam Shukry Ali; Nor Hafiza Haron; Nor Azura Salleh (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The education system has experienced major change since COVID-19, moving away from traditional learning methods and toward non-traditional solutions. Mobile learning is one of the most innovative methods of education that has emerged as a result of the widespread accessibility of information networks and ongoing technological advancement. This denotes the launch of an unconventional educational platform that makes use of mobile technologies to promote thorough knowledge gain and interactive learning. Students may show resistance to adopting mobile learning despite governmental efforts through its policy and benefits linked with educational technologies in learning. This hesitance is indicated by the conflicting findings present in the existing literature. The question of whether students possess favourable attitudes towards mobile learning remains an ongoing challenge to study. Hence, to illustrate thorough explanations regarding challenges related to the actual usage of mobile learning, the study intends to investigate the influence of perceived trust, perceived usefulness, perceived usability, perceived facilities, and perceived social influence of mobile learning. The study adopts these five (5) independent variables to test the dependent variable namely the actual use of mobile learning and treatment of the behaviour intention derived from the aforementioned five (5) independent variables. To fully illustrate, the study proposes a comprehensive framework for implementing mobile learning in public universities. The findings of the research offer practical advice on how to evaluate and improve the quality of mobile learning platforms and comprehend diverse factors for the effective use of mobile learning platforms.